INSTRUMENT DESIGN FOR CYBER RISK ASSESSMENT IN INSURABILITY VERIFICATION - Bartolini, David Nicolas; Ahrens, Andreas; Zascerinska, Jelena (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2018)
Cyber risk assessment for insurability verification has been paid a lot of research interest as cyber insurance represents a new dynamic segment of market with considerable growth potential for insurers. As customer’s practices and processes consistently lead to the final overall result, customer's behaviour has to be described in detail. The aim of the present paper is to design an instrument (questionnaire) for customer’s cyber risk assessment in insurability verification. The method for building an instrument (questionnaire) is empirical research. Empirical research is based on use of empirical evidence. A questionnaire with 11 questions is proposed.